Perilimnastes aura (Sonerileae, Melastomataceae), a new species from Dak Cheung Plateau, Sekong province, Southern Laos - Souvannakhoummane, Keooudone; Lamxay, Vichith; Lanorsavanh, Soulivanh; Liu, Ying (Phytotaxa, 2024)
Perilimnastes aura, a species found in Sekong province, Laos, is described as new. Its habit and morphology of leaves, inflorescences, flowers, and capsules match all diagnostic features of Perilimnastes. It most closely resembles P. suberalata in the quadrangular stems, unequal leaves, and glabrescent, oblanceolate to broadly elliptic leaf blade, but differs in the acute leaf apex (vs. acuminate), 1–3-flowered inflorescence (vs. 1-flowered), quadrangular hypanthium (vs. obtusely quadrangular) and broadly triangular, 1.8–2.2 mm long calyx lobes (vs. linear, 8–10 mm long). Information on habitat, ecology, and a preliminary assessment of the conservation status are also provided for the new species.